2020
DOI: 10.1186/s12903-020-1052-6
|View full text |Cite
|
Sign up to set email alerts
|

Using motivational interviewing to reduce parental risk related behaviors for early childhood caries: a pilot study

Abstract: Background: Decades of epidemiological studies have documented high rates of early childhood caries (ECC) among American Indian and Alaska Native (AIAN) children. The aim of this pilot study was to investigate if a motivational interviewing (MI) intervention improved oral self-care behaviors of AIAN caregivers of infants, and determine if the MI intervention promoted positive changes in caregivers' ECC risk-related behaviors. Methods: Caregivers of infants presenting for well-child visits in a medical clinic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…had similar findings as dentists reported, “there was only so much they could do if patients don't follow their recommendations.” 32 Behavior change is complex and the literature across health disciplines points to a limited understanding of how health professionals and their patients can achieve optimal behavior change 15 . A lack of positive behavior change is evident within MI literature, as many studies reported seeing no change in behavioral or clinical outcomes as a result of MI interventions 19,25–27 . Additionally, this finding may be attributed to nearly 10% of the respondents practicing in a non‐profit or a FQHC setting where social determinants of health impact behavior change 15,27,33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…had similar findings as dentists reported, “there was only so much they could do if patients don't follow their recommendations.” 32 Behavior change is complex and the literature across health disciplines points to a limited understanding of how health professionals and their patients can achieve optimal behavior change 15 . A lack of positive behavior change is evident within MI literature, as many studies reported seeing no change in behavioral or clinical outcomes as a result of MI interventions 19,25–27 . Additionally, this finding may be attributed to nearly 10% of the respondents practicing in a non‐profit or a FQHC setting where social determinants of health impact behavior change 15,27,33 .…”
Section: Discussionmentioning
confidence: 99%
“…A lack of positive behavior change is evident within MI literature, as many studies reported seeing no change in behavioral or clinical outcomes as a result of MI interventions 19,25–27 . Additionally, this finding may be attributed to nearly 10% of the respondents practicing in a non‐profit or a FQHC setting where social determinants of health impact behavior change 15,27,33 . Blue et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that MI interventions in dental health were mostly carried out on parents, caregivers, preschool children, patients with periodontal disease. 33,34,35,36,37 The lack of MI intervention research in adolescents. This study proves that MI is effectively implemented for adolescents.…”
Section: Discussionmentioning
confidence: 99%